2011
DOI: 10.1177/1947601911433129
|View full text |Cite
|
Sign up to set email alerts
|

HOXC8-Dependent Cadherin 11 Expression Facilitates Breast Cancer Cell Migration through Trio and Rac

Abstract: Cadherin 11 (CDH11) expression is detected only in invasive breast cancer cells and aggressive breast cancer specimens. However, little is known about the molecular mechanisms of CDH11 transcriptional regulation. Here, we report that interleukin enhancer binding factor 3 (ILF3) interacts with Homeobox C8 (HOXC8) to activate CDH11 transcription in breast cancer cells. Using co-immunoprecipitation and mass spectrometry analyses, ILF3 is shown to interact with HOXC8 in breast cancer cells. We demonstrate that ILF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…Although we could show that Trio binds to a region in VE-cadherin that is proximal to the β-cateninbinding domain, our experiments indicate that Trio does not seem to compete with β-catenin for binding to VE-cadherin but that it might in fact form a ternary complex. Previously, Trio has been reported to biochemically co-precipitate with M-cadherin, cadherin-11 and E-cadherin (Backer et al, 2007;Charrasse et al, 2007;Kashef et al, 2009;Li et al, 2012;Yano et al, 2011). In the latter study, the activity of Trio at E-cadherin-based epithelial cell-cell junctions is described as down regulating E-cadherin expression levels by activating a transcriptional repressor of E-cadherin (Yano et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Although we could show that Trio binds to a region in VE-cadherin that is proximal to the β-cateninbinding domain, our experiments indicate that Trio does not seem to compete with β-catenin for binding to VE-cadherin but that it might in fact form a ternary complex. Previously, Trio has been reported to biochemically co-precipitate with M-cadherin, cadherin-11 and E-cadherin (Backer et al, 2007;Charrasse et al, 2007;Kashef et al, 2009;Li et al, 2012;Yano et al, 2011). In the latter study, the activity of Trio at E-cadherin-based epithelial cell-cell junctions is described as down regulating E-cadherin expression levels by activating a transcriptional repressor of E-cadherin (Yano et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…e The bar chart of the relative protein expression of cleaved caspase-3 and Nkd2 in Huh7 cells under the indicated treatments. The data are mean ± SEM (* ,# P \ 0.05) Dig Dis Sci cancer [16], breast cancer [19]. Herein, we firstly demonstrated that HOXC8 might play an important role in the development of HCC.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in human prostate cancer cells, HOXC8 expression is not only correlated with loss of tumor differentiation [17], but also promoting invasiveness while inhibiting AR-mediated gene induction at androgen response element-regulated genes associated with differentiated function of the prostate [18]. In breast cancer, HOXC8-dependent cadherin 11 expression contributed to cell migration through Trio and Rac [19]. In addition, the ratio of miR-196s to HOXC8 mRNA might be an indicator of the metastatic capability of breast tumors [20].…”
Section: Introductionmentioning
confidence: 97%
“…The next question to consider is what makes Cad-11 unique in stimulating cell motility. Cad-11 in cranial neural crest cells of Xenopus (X-Cad-11) activates Rac, a Rho family GTPase, by promoting the enzymatic activity of Trio, a Rac GEF [46]. Trio and the membraneanchored cytoplasmic domain of X-Cad-11 work together to drive cell migration [47].…”
Section: Discussionmentioning
confidence: 99%